(untitled) (Revista Contexto & Saúde, 2025)
Objective: To assess levels of state and trait anxiety in preoperative patients admitted to the Surgical Unit of a hospital located in the extreme south of Brazil. Method: This quantitative, exploratory-descriptive study was conducted with 50 preoperative inpatients. Data were collected using the State-Trait Anxiety Inventory (STAI), translated and adapted for use in Brazil. Data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 22.0.2. Descriptive statistics were applied, and a t-test was performed to compare state and trait anxiety according to sex. Results: Trait anxiety scores were higher than state anxiety scores. Most participants exhibited trait anxiety rather than state anxiety, indicating that these preoperative patients already showed an anxious profile—that is, they possessed personality traits more prone to the development of anxiety. Conclusion: These findings are relevant to clinical nursing practice, considering that when professionals identify patients with anxiety symptoms, they must plan interventions that contribute to a calmer perioperative period and support postoperative recovery.